An 8‐year survey of strains identified in blood cultures in a clinical haematology unit. (4th July 2013) - Bousquet, A.; Malfuson, J.‐V.; Sanmartin, N.; Konopacki, J.; MacNab, C.; Souleau, B.; de, T.; Elouennass, M.; Samson, T.; Soler, C.; Foissaud, V.; Martinaud, C.; et al.
Abstract The aim of our study was to determine the epidemiological profile and the antibiotic susceptibility of bacteria and fungi identified from blood cultures in the patients of the clinical haematology unit. A retrospective study was carried out over an 8‐year period (2003–2010) in the clinical haematology unit of the Percy Military Medical Center. During this period, we collected 723 isolates: Gram‐negative bacilli (70.8%) and Gram‐positive cocci (18.7%). The four most commonly isolated species were Escherichia coli (18.5%), Pseudomonas aeruginosa (14.8%), Stenotrophomonas maltophilia (6.2%) and Staphylococcus epidermidis (5.4%). The rate of methicillin‐resistant Sthaphylococcus aureus was 6.45% and that of coagulase‐negative staphylococci 61.2%. No resistance to glycopeptides was observed. In E. coli, as in the Klebsiella‐Enterobacter‐Serratia group, a 27% resistance to fluoroquinolones was observed. Concerning P. aeruginosa, the phenotypes were distributed over penicillinase (23.4%) and cephalosporinase (13.1% were resistant to ceftazidime). The impermeability rate of imipenem was 9.3%. The aggressiveness and duration of haematological treatments explains why infections remain one of the main complications of neutropenia. The emergence of new or unusual bacteria is highly likely. Antibiotic selective pressure and long periods of hospitalization could explain the emergence of multiresistant bacteria. As a consequence, epidemiological surveillance is indispensable.